2009
DOI: 10.1080/19406940902950739
|View full text |Cite
|
Sign up to set email alerts
|

The power to shape policy: charting sport for development and peace policy discourses

Abstract: This paper discusses findings from a development policy discourse analysis that was conducted using six key sport for development and peace (SDP) policy documents. The research was guided by a theoretical framework combining postcolonial theory and actor-oriented sociology in order to critically analyse SDP policies. Based on this analysis, three theses are proposed: (1) SDP policies are unclear, circuitous and are underpinned by political rationalities; (2) coordinated and coherent SDP policy approaches betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 52 publications
1
114
0
1
Order By: Relevance
“…Moreover, critics have suggested that as a consequence of external pressures on SFD programs to "perform," there is a tendency to overstate positive program outcomes and associated impacts (Coalter, 2015). Additionally, in the absence of a critical SPORT-FOR-DEVELOPMENT IN THE SOUTH PACIFIC 5 foundation, Darnell (2012) argued that the increasing focus on monitoring and evaluation risks SFD becoming nothing more than a management function, and questions remain about programs' ability to address larger societal constraints and achieve meaningful structural change (see also Coalter, 2010;Darnell, 2010;Hayhurst, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, critics have suggested that as a consequence of external pressures on SFD programs to "perform," there is a tendency to overstate positive program outcomes and associated impacts (Coalter, 2015). Additionally, in the absence of a critical SPORT-FOR-DEVELOPMENT IN THE SOUTH PACIFIC 5 foundation, Darnell (2012) argued that the increasing focus on monitoring and evaluation risks SFD becoming nothing more than a management function, and questions remain about programs' ability to address larger societal constraints and achieve meaningful structural change (see also Coalter, 2010;Darnell, 2010;Hayhurst, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Canada, the UK, the USA and several Scandinavian countries have all been major players in funding for SfD. Even when projects are managed and delivered by local stakeholders and staff, there remains a noticeable imprint of Global North priorities and practices (Hayhurst, 2009). For example, Forde argues that 'SDP initiatives tend to align with discourses that emphasise individual responsibility and entrepreneurialism, and often promote universal and simplistic solutions to social problems at the expense of addressing broader structural factors ' (2013, p. 3).…”
Section: Why This Special Issue?mentioning
confidence: 99%
“…Embedded within a neoliberal discourse, SDP is said to replicate and perpetuate power relations that legitimise inequality and social hierarchy, justifying the contemporary status quo as it provides a remedy for social ills based upon an economic logic that promotes socio-political regulation at the expense of liberation (Darnell 2012;Hayhurst 2009;Li 2007). Furthermore, SDP programmes have been harnessed by nation states to reduce internal government spending on social care and health programmes, an approach to policy that reduces government responsibility for citizens in disadvantaged communities and is thus said to ignore the 'root causes' of poverty (Wilson and Hayhurst 2009).…”
Section: Sdp and The Importance Of Volunteer Identitymentioning
confidence: 99%
“…Recent work examining SDP has deployed frameworks that pursue Foucauldian notions of bio-power, Gramscian theories of hegemony and postcolonial theory to delineate a clearer appreciation of the structural negotiations that exist between sport, politics and culture, identifying the impact that such relations impose upon the articulation and delivery of policy processes located within the field of SDP (Black 2010;Darnell 2010Darnell , 2011Darnell , 2012Hartmannn and Kwauk 2011;Levermore and Beacom 2012;Hayhurst 2009;Tiessen 2011). Whilst such work provides invaluable critique for exposing the dominant power relations and structural imperatives that guide practices within SPD programmes, few studies pursue a line of examination that expose the beliefs, values and meanings through which practitioners make sense of their experiences.…”
Section: Introductionmentioning
confidence: 99%